Isolated ventricular non-compaction of the myocardium in adults. Issue 1 (2nd May 2006) - Jenni, R; Oechslin, E N; van der Loo, B
Abstract : Isolated ventricular non-compaction (IVNC) in adults is a genetic cardiac disease of emerging importance with a distinct clinical and pathophysiological presentation. The body of evidence for the underlying genetic basis of the disease has also grown. Prognosis remains poor for patients with impaired systolic left ventricular function, as treatment options are very limited. The diagnosis of IVNC, however, is often missed, most often as a consequence of ignorance of the condition. The relevant clinical issues and the emerging concepts of the aetiology of IVNC are summarised.